The Struggle of the Prophet Muhammad SAW in Building the ummah of Islam: A Story of Sacrifice and Courage - Nugraha, Ilah Nursolihah; Aulia, Salshabila; Tabroni, Imam; Wang, Yuanyuan; Zou, Guijiao (International Journal of Educational Narratives, 2023)
Background. Based on his life journey, the prophet Muhammad has always been a hot topic of conversation among the world's intellectuals (Ondeng, 2004). Da'wah is the main pillar in the teachings of Islam, because it has woven every story of the Prophet Muhammad's life. Purpose. In the midst of this difficult situation, the prophet Muhammad and his companions did everything they could to maintain the security and safety of Muslims. The emergence of these various problems shows that the truth of Islam is challenged to provide the right solution. Method. This research uses a literature study that collects and analyzes data related to the Prophet Muhammad's struggle in building Muslims. Results. Before Islam came through the prophet Muhammad, the Arabs believed in the existence of gods through the worship of idols and these were made of stone. During his childhood, Prophet Muhammad always contemplated the lives of the Jahiliyyah people and regularly visited the cave of Hira. On the 27th of Rajab in 610 AD prophet Muhammad was sent as an apostle. The Quran is a sacred revelation delivered directly by God to Prophet Muhammad. Conclusion. So based on the description above, the author will explain the struggle of the Prophet Muhammad to free Muslims from the grasp of the hands of the infidels. So compelling is the life of the Prophet Muhammad, a story colored by divine light and unwavering glory.